Circadian clock genes in insects - Bazalová, Olga (Jihočeská univerzita, 2017)
This thesis focuses on molecular characterization of circadian clock genes in insects. It explores genetic diversity of circadian clock genes by molecular characterization of several insect species including two dipteran flies (Musca domestica and Drosophila melanogaster), two cockroach species representing ancestral insects, and the linden bug, Pyrrhocoris apterus. Furthermore it considers various roles of circadian clock genes in insect physiology. Application of molecular-biology methods in Pyrrhocoris apterus, non-model insect species, enable us to investigate involvement of circadian clock genes in photoperiod induced physiological responses. Application of molecular-biology methods in Periplaneta americana and Blattella germanica was used to explore involvement of circadian clock genes in magnetoreception.
Circadian clock genes in insects
Keywords: circadian; photoperiodic; clock; genes; insects; magnetoreception; circadian; photoperiodic; clock; genes; insects; magnetoreception